Festivals and Music as a Tourism Attraction: A Bibliometric Analysis - Judijanto, Loso; Nailul, Muhammad (Westscience Press, 2025)
Festivals and music events have become integral components of tourism development, offering cultural enrichment, economic stimulation, and unique visitor experiences. This study conducts a comprehensive bibliometric analysis to map the intellectual, conceptual, and geographical landscape of academic research on festivals and music as tourism attractions. Using data retrieved from the Scopus database and analyzed through VOSviewer, the study examines the co-occurrence of keywords, co-citation patterns among authors, and international collaboration networks. The results identify central themes such as cultural tourism, tourist behavior, and event marketing, with emerging interest in sustainability, music tourism, and digital engagement. Influential authors including Getz, Gibson, and Richards are highlighted as key intellectual contributors, while dominant research hubs are located in the United States, United Kingdom, and Australia. The findings reveal a dynamic and evolving field, with strong interdisciplinary linkages and opportunities for expanded research in underrepresented regions and novel event formats. This analysis provides a foundational reference for scholars, practitioners, and policymakers aiming to advance the understanding and strategic development of festival and music tourism.